Philippine disaster preparedness systems for natural hazards an assessment - Punongbayan, R.S (Philippine Journal of Public Administration, 1993)
The Philippines is vulnerable in varying degrees to natural hazards in the form of typhoons, floods, landslides, volcanic eruptions, earthquakes, tsunami, seiche, storm surges and sea-level changes. These highly undesirable conditions are offshoots of the tectonic, geologic, geographic and physiographic settings of the Philippine Archipelago. The vulnerability of the Philippines to said natural hazards requires the emplacement of effective disaster preparedness and/or avoidance systems. The Philippines partly succeeded in satisfying the needs of a viable monitoring system by establishing monitoring networks for typhoons, active volcanoes and earthquakes. Its prediction system works only for typhoons and storm surge forecasting and invariably for volcanic eruption forecasting. We are now in the process of experimenting on flood forecasting. The response system is already in place but needs to be strengthened via intensive promotion of public awareness on natural hazards and disasters with the active support of the broadcast and print media. By and large, therefore, the country's disaster preparedness systems are presently highly porous.